Repeated intraspecific divergence in life span and aging of African annual fishes along an aridity gradient - Blažek, Radim; Polačik, Matej; Kačer, Petr; Cellerino, Alessandro; Řežucha, Radomil; Methling, Caroline; Tomášek, Oldřich; Syslová, Kamila; Terzibasi Tozzini, Eva; Albrecht, Tomáš; Vrtílek, Milan; Reichard, Martin (Evolution, 2017)
Life span and aging are substantially modified by natural selection. Across species, higher extrinsic (environmentally related) mortality (and hence shorter life expectancy) selects for the evolution of more rapid aging. However, among populations within species, high extrinsic mortality can lead to extended life span and slower aging as a consequence of condition-dependent survival. Using within-species contrasts of eight natural populations of Nothobranchius fishes in common garden experiments, we demonstrate that populations originating from dry regions (with short life expectancy) had shorter intrinsic life spans and a greater increase in mortality with age, more pronounced cellular and physiological deterioration (oxidative damage, tumor load), and a faster decline in fertility than populations from wetter regions. This parallel intraspecific divergence in life span and aging was not associated with divergence in early life history (rapid growth, maturation) or pace-of-life syndrome (high metabolic rates, active behavior). Variability across four study species suggests that a combination of different aging and life-history traits conformed with or contradicted the predictions for each species. These findings demonstrate that variation in life span and functional decline among natural populations are linked, genetically underpinned, and can evolve relatively rapidly.
Keywords: Cyprinodontiformes; zvláštnosti životní historie; Male; Aging; Longevity; dlouhověkost; podnebí; Climate; biologická evoluce; mužské pohlaví; Selection, Genetic; selekce (genetika); Animals; ženské pohlaví; Biological Evolution; zvířata; stárnutí; Female; Life History Traits